2022
DOI: 10.3390/ijerph19159501
|View full text |Cite
|
Sign up to set email alerts
|

Underdog Environmental Expectations and Environmental Organizational Citizenship Behavior in the Hotel Industry: Mediation of Desire to Prove Others Wrong and Individual Green Values as a Moderator

Abstract: Discretionary environmental behaviors are usually encouraged beyond a formal reward system, but environmental skeptics, from managers or co-workers, place underdog expectations on the importance of organizational citizenship behaviors for workplace environments. Building on the leadership substitution theory, the social exchange theory (SET), and the ability-motivation-opportunity (AMO) theory, in the current study, we explore the relationships between underdog environmental expectations and organizational cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…Most HTMT values have to be less than 0.90(Gold et al, 2001). The values of the HTMT in this study were lower than those values shown in Table4.…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…Most HTMT values have to be less than 0.90(Gold et al, 2001). The values of the HTMT in this study were lower than those values shown in Table4.…”
contrasting
confidence: 69%
“…Third, the convergent validity of the model structure was assessed by the values of AVE "Average Variance Extracted", which are above the acceptable value of 0.50. (Henseler et al 2009;Elshaer et al 2022c).…”
Section: Assessment Of Outer Measurement Modelmentioning
confidence: 99%
“…As a result, the findings revealed in our study add to green management and behaviour theory and practice, as well as the SME literature. Finally, the study recommends supporting the employees' pro-environmental behaviour to stimulate them to cope with environmental issues through task coping styles [111] to raise their expectations regarding sustainable performance [112]. Thus, this would overcome the obstacles of greening in small-and medium-sized hospitality businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Paillé and Raineri [ 18 ] indicated that companies with stronger environmental policy support have higher OCBE. Moreover, OCBE can not only take the managerial engagement and organizational sustainability into account [ 19 , 20 ], but also create spiritual leadership [ 21 ]. Thus, OCBE has become increasingly important in various fields [ 22 , 23 , 24 ].…”
Section: Theoretical Foundation and Research Hypothesesmentioning
confidence: 99%